Contributions of the phenomenographic approach for information literacy learning and education - Ernesto Manhique, Ilidio Lobato [UNESP]; Silva Casarin, Helen de Castro [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2020)
The complexity of digital environment derived from the growing volume of data and information requires a set of skills, atitudes and knowledge that favor people autonomous learning. The information literacy is part these assumptions that allow critical and reflexive use of information. This research explores the phenomenographic approach to investigate the learner-based learning and its impact on information literacy education. Based on literature review, this research provides insights about the importance of phenomenography to conceive relational models of information literacy, which can be an alternative to the prevailing standards and frameworks which categories of description are defined priori. In this work were analyzed two relational models of information literacy, namely, seven faces of information literacy and six frames for information literacy education, to demonstrate how phenomenography has been used to examine the relation between individuals and information. It concludes that phenomenograpy is an approach with unlimited potentialities to help to design and redesign information literacy programs in several educational levels. Given the incipiency of this kind of studies in Brazilian context, we suggest that new studies about information literacy using phenomenographic perspective are necessary in order to deepen the theoretical and methodological bases of information literacy learning and education.
Keywords: Phenomenography; Information literacy; Relational model; Learning; Education